Towards Equity? Advancing Rural Consideration in Flood Risk Management - Daniel W. A. Jones; Fiona Williams; Namrata Bhattacharya Mis; Philip M. Marren (Journal of Flood Risk Management)
ABSTRACT Flood risk management (FRM) in England and Wales predominantly follows a utilitarian approach guided by cost–benefit analysis, with a corresponding focus on urban areas. This approach has been criticised for being unjust, as it neglects vulnerabilities that cannot be readily monetised, resulting in some of the most vulnerable flood‐affected communities being excluded from FRM provision. This issue is especially pronounced in rural areas. Ironically, rural communities are often overlooked despite many contributing to the protection of urban settlements. In response to increasing research on social injustices in FRM and policy calls for more equitable approaches, greater consideration of rural flooding is required. Using the River Severn catchment as a case study, this paper employs a questionnaire survey of 176 rural residents to gather perspectives on their engagement with FRM agencies. Their responses were then discussed with FRM organisations active in the region through interviews. The combined perspectives of rural communities and FRM organisations reveal challenges and opportunities for achieving just consideration of rural areas in FRM. The findings emphasise the need for a more inclusive approach to FRM in the River Severn catchment and offer valuable lessons for other rural areas in the United Kingdom and beyond.